Determination of Shear Capacity for Load Rating of Concrete Bridges to AS 5100.7-2017 - Koon Wan Wong; Vanissorn Vimonsatit (Infrastructures, 2022)
According to Modified Compression Field Theory (MCFT), the ultimate shear capacity of a reinforced concrete section depends on load effects (shear, moment, torsion, and axial force) caused by factored design loads. In many design standards, including Australian AS 5100.7, MCFT has been incorporated for bridge assessment, which requires a load rating to be carried out according to the loading of the nominated rating vehicle as prescribed in the standard. Recently, some approaches have been proposed for bridge load rating that have suggested using an iterative-search procedure to determine the shear capacity by proportionally increasing the load effects until the shear capacity and shear are equal. This paper describes several adverse effects of using the proportional load, which is not consistent with the characteristic of the vehicle loading, to determine the shear capacity for load rating. Numerical examples of two bridge beams, one simply supported and the other continuous, are presented to demonstrate that the characteristic of the load effects caused by a moving vehicle is not representable by proportional load effects. Furthermore, the current practice in the bridge load rating does not load rate the longitudinal steel capacity in resisting the axial force induced by the load effects of the rating vehicle. This paper presents a new approach to the load rating that separately accounts for the load effect for axial failure mode of the longitudinal steel. Finally, it is pointed out that locating the critical section where the rating factor is minimum is tedious but can be automated by integrating load rating into the analysis of load effects.